Generalized tuberculosis and multifetal pregnancy - P. O. Sotskiy; L. G. Gevorkyan; O. L. Sotskaya; M. D. Safaryan (Туберкулез и болезни лёгких)
The article describes a clinical case of successful treatment of generalized tuberculosis in a young immunocompetent woman with multifetal pregnancy (triplets) and multiple localizations of tuberculosis: tuberculosis meningitis, disseminated pulmonary tuberculosis, and uterine tuberculosis. Specific parameters of tuberculosis diagnostics in the pregnant are presented.